Gender features of self-description of schoolchildren’s physical condition - Krutsevich, T.Yu.; Marchenko, O.Yu. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study age and gender features of schoolchildren’s attitude to their physical “self”. Material: in the research pupils of 5-11 forms (n=365) participated. They were: 177 boys and 188 girls. Individual profile of personality’s physical “self” was studied. For this purpose test-questionnaire was used and self description of physical condition. Results: it was found that self assessment of schoolchildren’s physical condition was too high. It was in average 80-85% from maximal indicator. It was also found that by all indicators sportsmen had higher self-esteem. For development of boys and girls’ individual abilities and bents, overcoming of gender-role stereotypes it is necessary to have knowledge about sex and gender specificities of schoolchildren’s physical development as well as about their influence on self esteem and formation of physical qualities. Conclusions: we showed that it was possible to correct physical education curriculum and its implementation in educational process.